(untitled) (Intercom - Brazilian Journal of Communication Sciences, 2023)
The structure and agency of digital platforms, especially social networks and messaging services, are essential media content distributors in democratic societies. We examine the evolution of the web, highlighting questions about transparency and the use of personal data by technology giants. We offer a critical perspective on the business model of these platforms, exploring conflicts of interest, public values, and everyday goods, as well as the impact on the spread of misinformation. We carried out a survey that reveals the deliberate use of disinformation on social networks and messaging services as a political weapon in the 2022 presidential elections. We also point out the legal resources used in the fight against it.